A temporo-spatial analysis of the neural correlates of extrinsic perceptual grouping in vision. (March 2015) - Montoro, Pedro R.; Luna, Dolores; Albert, Jacobo; Santaniello, Gerardo; López-Martín, Sara; Pozo, Miguel A.; Hinojosa, José A.
Abstract: Principles of perceptual grouping can be divided into intrinsic grouping cues, which are based on built-in properties of the grouped elements (e.g., their shape, position, colour, etc.) like most of the classical Gestalt laws, and extrinsic grouping principles, based on relations between the discrete elements and other external stimuli that induce them to group (e.g., common region, connectedness). Several studies have explored the neural correlates of intrinsic grouping factors but, to our knowledge, no previous study has studied the neural correlates of extrinsic principles. The present study aimed to shed light on this issue by exploiting the high temporal resolution of event-related potentials (ERPs) and recent advances in source localization. Specifically, grouping by common region was compared with two comparison conditions, an intrinsic grouping (luminance similarity) and a uniform stimulus condition, in a perceptual discrimination task. We reported three main neural effects associated with grouping by common region. First, a posterior N210 component with a neural origin in the left extrastriate cortex was related to perceptual analysis of extrinsic elements inducing grouping and the formation of a visual group. Second, an enhanced posterior P280, which presumably reflects higher confidence decisions during response selection. Finally, a P550 originated in the right superior parietal cortex that seems to be associated with top-down suppression activity connected with the termination of the processing of the current trial. Overall, our results suggest that common region cues belong to the category of long latency grouping principles that mainly involve activity in extrastriate cortices. Highlights: We studied the neural correlates of common region, an extrinsic grouping principle. Several ERP effects and their neural sources were associated to common region. Our results characterized common region as a long latency grouping principle. Perceptual processing of common region seems mainly governed by extrastriate cortex.